How galaxies populate haloes in very low-density environments: An analysis of the halo occupation distribution in cosmic voids - Alfaro, Ignacio Germán (2020)
Evidence shows properties of dark matter haloes may vary with large-scale environment. By studying the halo occupation distribution in cosmic voids it is possible to obtain useful information that can shed light on the subject. The history of the formation of the haloes and galaxies residing in these regions is likely to differ from the global behaviour given their extreme environment. We use two public access simulated galaxy catalogues constructed with different methods: a semi-analytical model and a hydrodynamic simulation. In both, we identify cosmic voids and we measure the halo occupation distribution inside these regions for different absolute magnitude thresholds. We compare these determinations with the overall results and we study the dependence of different characteristics of the voids. Also, we analyze the stellar content and the formation time of the haloes inside voids and confront the general halo population results. Inside the voids, we find a significantly different halo occupation distribution with respect to the general results. This is present in all absolute magnitude ranges explored. We obtain no signs of variation related to void characteristics indicating that the effects depend only on the density of the large-scale environment. Additionally, we find that the stellar mass content also differs within voids, which host haloes with less massive central galaxies (10%) as well as satellites with significantly lower stellar mass content (30%). Finally, we find a slight difference between the formation times of the haloes which are younger in voids than the average population. These characteristics indicate that haloes populating voids have had a different formation history, inducing significant changes on the halo occupation distribution.